Identification of Netizen Communication regarding the Issue of the National Capital Relocation Plan # IKN Nusantara on Twitter - Joego Herwindo; Bherta Sri Eko Murtiningsih; Rismi Juliadi (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
The plan to move the capital city of the Republic of Indonesia (RI) from DKI Jakarta Province to East Kalimantan Province sparks pros and cons. Various comments appeared on social media. This study aims to: (1) find out the issues carried in the #IKNNusantara hashtag network; (2) categorize comments into negative, positive, and neutral sentiment categories; (3) find the structure and relationships of the actors in the network. The research methodology is quantitative research approach, the SNA (Social Network Analysis) method using NodeXL software and Sentiment Analysis using the online application Brand24.com on the hashtag #IKNNusantara on Twitter. The results of sentiment analysis show that the conversation is dominated by neutral sentiment. The total number of tweets up to February 16, 2022, was 255. SNA results show that the network density between actors in #IKNNusantara is still low at 0.23 percent. The network diameter describes the network pattern spreads and the cohesiveness between actors is low. The most influential actors based on the value of centrality are the accounts @jokowi and @ir with the highest in-degree values, which shows that a lot of talks are directed to this account. Accounts @d_n4bil5 and @newiding30 who have the highest out-degree are the most active in disseminating information. The @jokowi and @d_n4bil5 accounts serve as bridges because they have the highest betweenness value. Accounts @doddyjasmar and @royadam_lubis have the highest closeness values. Furthermore, the @d_n4bil5 and @langonlegend accounts with the highest eigenvector values are the actors with the most links to other actors. With this result, the government needs to continue to monitor the issue continuously and build awareness among netizens and the Indonesian people in general about the importance of IKN development. The use of social media focusing on delivering messages through the 7 (seven) most influential accounts above can have a significant impact. In terms of issue management, the government also needs to consider the most appropriate strategies to respond to issues according to the type of issue and the government's position on the issue.